When the grass wasn't greener: Megafaunal ecology and paleodroughts. (15th August 2021) - Rozas-Davila, Angela; Correa-Metrio, Alex; McMichael, Crystal N.H.; Bush, Mark B.
Abstract: A 42, 000-year record of coprophilous fungal ( Sporormiella, Podospora, Cercophora ), fossil pollen and charcoal data assessed megafaunal use of woodland versus grassland settings in Central American landscapes by Pleistocene megafauna. The sedimentary record from Lake Petén-Itzá showed that vegetation growing around the lake shifted between scrub grasslands, Pinus -dominated woodlands, Quercus -dominated woodlands, and tropical seasonal forest. A series of regression analyses and probabilistic models revealed that vegetation assemblages and temperature influenced the abundance of coprophilous fungus, a proxy for megafaunal abundance. We found that megafaunal populations were almost continuously present around Petén-Itzá during the Pleistocene, and that the peak abundances appear to have been associated with cool, moist Quercus -rich parklands. In contrast, the lowest inputs of coprophilous fungi occurred during cold, dry events when scrub grasslands expanded. The dry grasslands may have been nutrient-limited, offering poor quality grazing for megafauna. The decline of the Pleistocene megafauna at Petén-Itzá was a multi-stage event, with a series of population collapses prior to an inferred local extirpation c. 13, 600 years ago. Highlights: Dung spores provide 42, 000 years record of megafaunal history from Lake Petén-Itzá. Climatic and vegetation changes were statistically linked to megafaunal abundance. Wet interstadials favored browsers; cold-dry Heinrich events did not favored grazers. Nutrient poor grasslands formed during Heinrich events limiting grazer abundances. Megafauna disappeared 13, 600 years ago, but the human role could not be demonstrated.